Community-Based Diabetes Prevention through Diabetes Education and Exercise for Family Welfare Movement (PKK) - Sulistyorini, Anita; Puspitaningtyas, Dian; Rachmawati, Windi Chusniah; Valent, Amel Naysilla; Malita, Cintya Nur; Fathin, Jihan Rona Sausan Fathin Rona Sausan; Ratnasari, Miwa; Salsabila, Najwa; Garnisa, Rachmalia Zahwa (Universitas Padjadjaran, 2026)
Community service activities were conducted in Kalirejo Village, Lawang Subdistrict, Malang Regency, targeting the women of the PKK RW 04 as the primary beneficiaries. The objective of this initiative was to enhance understanding of the importance of physical activity in preventing Diabetes Mellitus, particularly among the aging population. The activity was conducted over two sessions, including diabetes exercises, health check-ups, and educational sessions on diabetes and physical activity. The pre-test and post-test results showed an average score increase from 81.6 to 89.14, indicating an improvement in participants' knowledge after attending the educational sessions on diabetes and physical activity. Based on health check-ups, the 50-59 age group was identified as the highest-risk group, with an average body mass index of 29.9 (obesity) and an average blood sugar level of 133 mg/dL. Metabolic disorders in the 30-39 age group underscore the importance of prevention starting at a productive age to reduce the risk of diabetes. Overall, this activity was deemed effective in enhancing participants' awareness and understanding of the importance of maintaining a healthy lifestyle as a preventive measure against diabetes, particularly for the productive age group. Keywords: Physical activity; diabetes; gymnastics